Addressing of Global Environmental Problems and the Solutions: A Bibliometric Analysis - H. Husamah; Vivi Indriani; Hanik Fitrotul Azizah; Abdulkadir Rahardjanto; Tutut Indria Permana; Ahmad Adnan Mohd Shukri (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Environmental problems and their solutions demand a holistic approach to address key challenges effectively. Previous studies have included reviews but lacked bibliometric analysis. This study bridges the gap by conducting a bibliometric analysis of research on